2001
DOI: 10.4269/ajtmh.2001.64.119
|View full text |Cite
|
Sign up to set email alerts
|

Canine visceral leishmaniasis in Colombia: relationship between clinical and parasitologic status and infectivity for sand flies.

Abstract: Abstract. We studied the reservoir competency of canines with distinct clinical presentations of Leishmania chagasi infection. The parasitologic status of asymptomatic and symptomatic dogs was determined by standard culture methods Infectivity was assessed by multiple xenodiagnoses with Lutzomyia longipalpis, over a period of 2-11 months. Asymptomatic dogs were non-infective (0 of 5) while 2 of 7 oligosymptomatic dogs infected L. longipalpis, transmitting the parasites at low rates (range 0.9-5.2% of engorged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
112
2
28

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(163 citation statements)
references
References 34 publications
11
112
2
28
Order By: Relevance
“…Nevertheless, the observations made on these two dogs contrasted with xenodiagnoses performed on dogs infected with L. infantum in which parasites are readily transmitted to sand flies, including non-natural vector species (20)(21)(22). In our case, the low reservoir competence was emphasized by the negative results obtained with Lutzomyia trapidoi, L. gomezi, and L. youngi, which are proven vectors of cutaneous leishmaniasis (13,15), and have shown to acquire Leishmania at high rates (37-44%) after feeding on laboratory animals experimentally infected with L. Viannia (23; CIDEIM unpublished).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, the observations made on these two dogs contrasted with xenodiagnoses performed on dogs infected with L. infantum in which parasites are readily transmitted to sand flies, including non-natural vector species (20)(21)(22). In our case, the low reservoir competence was emphasized by the negative results obtained with Lutzomyia trapidoi, L. gomezi, and L. youngi, which are proven vectors of cutaneous leishmaniasis (13,15), and have shown to acquire Leishmania at high rates (37-44%) after feeding on laboratory animals experimentally infected with L. Viannia (23; CIDEIM unpublished).…”
Section: Discussionmentioning
confidence: 88%
“…and establish the reservoir role in Colombian foci of American cutaneous leishmaniasis. Studies in Brazil have shown that the majority of lesions were localized on the ears (63.6% of all lesions detected), and this may have epidemiological implications because in other Leishmania species (L. infantum) we determined that transmission to sand flies was more efficient at this site than in other body areas (21,25).…”
Section: Discussionmentioning
confidence: 90%
“…Em áreas urbanas, cães domésticos são considerados os principais reservatórios de Leishmania chagasi e embora a doença possa manifestar-se de maneira bastante variável, o parasitismo da pele constitui uma das características mais importantes, fazendo desse animal um elo no ciclo epidemiológico 13 . A retirada de cães sororreatores das áreas endêmicas, ainda é um assunto polêmico.…”
Section: Discussionunclassified
“…Previous studies concerning the infectivity of dogs naturally parasitized by L. infantum to sandflies showed divergent results 9,16,18 . In general, asymptomatic dogs are either non-infective 18 or modest sources of infection 15 , while symptomatic dogs are often infective 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, asymptomatic dogs are either non-infective 18 or modest sources of infection 15 , while symptomatic dogs are often infective 18 . Indeed, every infected dog must be seen as a potential risk to phlebotomine sandfly infection.…”
Section: Introductionmentioning
confidence: 99%